MEASURING PROJECT PROFITABILITY: RATE OF RETURN OR PRESENT VALUE–A REJOINDER. - Wright, F. K. (The Accounting Review, 1963)
This article presents the author's rejoinder as J. W. Bennett accuses him of having made several important errors in his article on corporate profits. In fact, he has convicted him of one error only: It was the mistake of double counting retained earnings and his discussion of earnings yield therefore needs to be modified. A substantial part of Mr. Bennett's attack consists of an arithmetical demonstration of the fact that the present-value ranking of two projects may vary with the rate at which their cash flows are discounted. This fact is not in dispute. The point at issue is whether the rate at which stockholders discount future yields is more relevant to the assessment of project profitability than the earning rate of the marginal project. Mr. Bennett thinks that the stockholders' discount rate is always more relevant, whereas he considers it irrelevant when it lies below the earning rate of the marginal project. In this situation, corporation management would set itself a growth target which is consistent with an acceptable cut-off rate; and that, within the limits imposed by this constraint, it would wish to select the more profitable of the opportunities available to it.